The Class I HDAC Inhibitor Valproic Acid Strongly Potentiates Gemcitabine Efficacy in Pancreatic Cancer by Immune System Activation - Amber Blaauboer; Peter M. van Koetsveld; Dana A. M. Mustafa; Jasper Dumas; Fadime Dogan; Suzanne van Zwienen; Casper H. J. van Eijck; Leo J. Hofland (Biomedicines, 2022)
Background: Gemcitabine efficacy in pancreatic cancer is often impaired due to limited intracellular uptake and metabolic activation. Epi-drugs target gene expression patterns and represent a promising approach to reverse chemoresistance. In this study, we investigate the chemosensitizing effect of different epi-drugs when combined with gemcitabine in pancreatic cancer. Methods: Mouse KPC3 cells were used for all experiments. Five different epi-drugs were selected for combination therapy: 5-aza-2′-deoxycytidine, hydralazine, mocetinostat, panobinostat, and valproic acid (VPA). Treatment effects were determined by cell proliferation and colony forming assays. Expression of genes were assessed by real-time quantitative PCR. The most promising epi-drug for combination therapy was studied in immune competent mice. Intratumor changes were defined using NanoString PanCancer panel IO360. Results: All epi-drugs, except hydralazine, potentiated the gemcitabine response in KPC3 cells (range decrease IC50 value 1.7–2-fold; p < 0.001). On colony formation, the cytotoxic effect of 0.5 ng/mL gemcitabine was 1.4 to 6.3 times stronger (p < 0.01). Two out of three drug-transporter genes were strongly upregulated following epi-drug treatment (a range fold increase of 17–124 and 9–60 for Slc28a1 and Slc28a3, respectively; all p < 0.001). VPA combined with gemcitabine significantly reduced tumor size with 74% compared to vehicle-treated mice and upregulated expression of immune-related pathways (range pathway score 0.86–1.3). Conclusions: These results provide a strong rationale for combining gemcitabine with VPA treatment. For the first time, we present intratumor changes and show activation of the immune system. Clinical trials are warranted to assess efficacy and safety of this novel combination in pancreatic cancer patients.